Prosthodontic rehabilitation of a mucormycosis patient: a case report - Anand, Chinta; Sajjan MC, Suresh; Bheemalingeswara Rao, D; Mantena, Satyanarayana Raju; Rajesh Kumar, PV; Kondaveethi, Bharth (International Journal of Dental Materials, 2022)
Maxillofacial defects can result from congenital disabilities, cancer surgery, trauma, infection, or disease. Facial deformities can affect how a person looks, feels about themselves, and interacts with others. It can significantly impair phonetics, mastication, and deglutition and cause facial deformation. Maxillectomy due to mucormycosis is one such maxillofacial defect and it becomes essential to rehabilitate these cases with modified techniques based on the extension of intraoral defect, the severity, the degree of resection, the type of mucormycosis, the stability of lesions over time, the presence of contiguous disease, the accessibility of dental and prosthetic resources, and patient expectations. The prosthetic reconstruction with a maxillofacial prosthesis can restore function and appearance, comfort, and quality of life. The prosthesis should be simple to handle, easy to maintain, biocompatible, light in weight, and convenient for future adjustments. The maxillofacial surgeon, oncologist, and reconstructive dentist should work together to develop a treatment plan based on these considerations. This case report provides the current treatment options for these patients and rehabilitation of the defect. It also discusses the issues that need to be addressed during the planning of prosthetic treatment and highlights some challenges the clinicians face in providing prosthetic treatment for mucormycosis patients.